Self-monitoring of intraocular pressure in glaucoma. (3rd September 2019) - Beck, Daniel; Tatham, Andrew J.
ABSTRACT: Introduction : The widespread availability of wearable sensors such as smart watches and activity trackers has made self-monitoring of parameters including heart rate mainstream. Self-monitoring is also central to the management of diseases including diabetes and hypertension. New technologies are also now available that enable self-monitoring of intraocular pressure (IOP), with the potential to improve management of glaucoma. Areas covered : The aim of this review is to critique current evidence for the role of self-monitoring of IOP in glaucoma. Topics covered included the history of self-tonometry, the reliability of measurements obtained and the potential for self-monitoring devices to be used in telemedicine. Expert opinion : Self-tonometry has been shown to be achievable in most patients, with measurements showing reasonable agreement with Goldmann applanation tonometry. Self-tonometry has the advantage of allowing multiple IOP measurements to be obtained providing greater insight into IOP fluctuations and potentially improving our ability to determine treatment effect. Although no studies were found assessing cost effectiveness, self-tonometry could be used to replace office hour phasing, a costly and labor-intensive practice. In the future, artificial intelligence may be helpful in the interpretation of large streams of data produced by self-tonometry.